Incidental misplacement of a percutaneous nephrostomy tube in the inferior vena cava - Potić, Milan; Ignjatović, Ivan (Vojnosanitetski pregled, 2021)
Introduction. An isolated renal pelvis rupture is a rare type of blunt renal trauma that can occur mostly in patients with pre-existing hydronephrosis due to different causes. We presented a patient with the misplacement of a percutaneous nephrostomy tube during the treatment of isolated renal pelvis rupture in a patient with pre-existing hydronephrosis caused by post-irradiation ureteral stricture. Case report. A 36-year-old woman was referred to our institution by her gynaecologist for the treatment of a retroperitoneal urinoma. She had completed the irradiation treatment with concurrent cisplatin chemotherapy for a uterine malignancy one year ago. A computed tomography scan showed an isolated rupture of the left renal pelvis with the pre-existing hydronephrosis. A nephrostomy catheter was misplaced in the inferior vena cava during the percutaneous urinary drainage attempt. The patient underwent a laparotomy, renal pelvis suture and ureteroneocystostomy with an indwelling double pigtail stent. The percutaneous nephrostomy was removed during the same surgical procedure. Conclusion. Inadvertent injury of vascular structures is a possible complication of percutaneous nephrostomy under ultrasound guidance. It may have been possible to avoid the reported complication if the dilation of the nephrostomy tract over the guidewire had been performed under contrast-enhanced X-ray fluoroscopy.
Keywords: hydronephrosis; intraoperative complications; nephrostomy, percutaneous; tomography, x-ray computed; urologic surgical procedures; vena cava, inferior